Effect Of Oxytocin Massage With Lavender Essential Oil On Breast Milk Production In Postpartum Mothers - Romzalina, Dian Eka; Yulianto, Yulianto; Suprida, Suprida; Nursanti, Rina (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
Decreased production and expenditure of Mother's Milk (ASI) can be caused due to lack of stimulation of the hormones prolactin and oxytocin which play an important role in the production of mother's milk. One effort that can be done to increase milk production is Oxytocin Massage with Lavender Essential Oil. Purpose: This research aims to determine the Effect of Oxytocin Massage with Lavender Essential Oil on Breast Milk Production in Postpartum Mothers at PMB Palembang City in 2023. This type of research is quantitative with Quasi experiment and group pretest-posttest design. The researcher used the accidental sampling technique by taking a sample of 33 respondents. The research instrument used the Standard Operating Procedure Sheet and the Observation Sheet for the Amount of Breast Milk Production. Data analysis used the Wilcoxon test. The results : of the study showed that the average value of breast milk production in postpartum mothers before being given the intervention was 5.15 and after being given the intervention it increased by 28.76. with the results of statistical tests p-value 0.001 (α <0.05). Conclusion: There is an effect of Oxytocin Massage with Lavender Essential Oil on Breast Milk Production in Postpartum Mothers at PMB Hj. Herasdiana and PMB Hj. Kustirah Palembang City in 2023. Suggestion: This research can be an alternative in the care of postpartum mothers who breastfeed with insufficient milk production.